Current Understanding of Inflammatory Responses in Acute Kidney Injury - Hu, Chao; Sheng, Yue; Qian, Zhijian (Current Gene Therapy, 2017)
Acute kidney injury has been a tough complex with increased mortality and morbidity. Inflammatory responses, including innate and adaptive immune responses, involve in the initiation and development of acute kidney injury, especially under the ischemic circumstances. Tubular cells and distinct immune cell subgroups play a critical role in the pathogenesis of inflammation. Current gene therapies show their benefits in renal repair. Here, we reviewed the renal inflammatory infiltration, inflammatory mediators, oxidative stress and potential signaling pathways, which give rise to the kidney diseases, in the mechanism of acute kidney injury. Recent studies showed diverse insights in understanding the pathophysiological process of inflammation related renal injury and provided novel clinical targets for ameliorating acute kidney injury by balancing the facilitation of repairing and prevention of impairing. Interestingly, antisense oligonucleotides of target sequence, local electransfering on solid organ and adenovirus-mediated certain gene overexpression have been promising strategies in alleviating acute kidney injury.
Keywords: Acute kidney injury